Analisis Perbandingan Algoritma Prefix Code Dengan Elias Omega Code Dalam Merancang Aplikasi Pengkompresi File Video Avi - Arby Hartama (STMIK Budi Darma, 2022)
In the field of information technology, data storage is usually carried out by transmitting data using an electronic transmission system. The large size of the data file becomes an obstacle in sending data with a large size which will take quite a long time, especially in video files. Video files are information media that are often used. In general, AVI video files are quite large file formats. So with the research conducted using the Prefix code algorithm and the elias omega code algorithm to compress video files and to perform comparisons, because the second algorithm has a different way of working. Given this difference, a scan is needed to compare the two algorithms to determine which file compression is faster. The exponential method is a method that allows you to perform a comparative analysis of two algorithms. Thus, we can see which yahoo is the best, efficient and fast to compress video files